Existenzgründerpotentiale unter Arbeitsuchenden: Empirische Evidenz auf der Basis des Mikrozensus - Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
In April 1995, 5.3 million people in Germany were on the lookout for a new job opportunity. 177,000 or nearly 3% of those were searching for an opportunity to get self-employed. In this study the determinants of the lookout for selfemployment in lieu of wage work are investigated separately for East and West Germany. Using the 70 %-ZEW-sample of the ?Mikrozensus? of 1991, 1993 and 1995, there is evidence that the probability of the search for self-employment depends, among other factors like age, sex and education, on the status in the labour market. In 1991 in East Germany the probability of aspiring to self-employment was higher for the unemployed than for the employed and decreasing by the time. In West Germany it was higher for the employed than for the unemployed and decreasing as well. By 1995 there was no difference anymore. Higher unemployment rates since 1993 in combination with transition payments for the unemployed to start their own business can explain these findings.
Keywords: C35; J68; D92; 330; Arbeitsuche; Unternehmensgründung; Selbstständige; Schätzung; Arbeitslosigkeit; Deutschland